Le premier mouvement pour la protection des animaux dans les États allemands (1820-1860) - Thomas Nicklas (Recherches Germaniques)
After the revolutionary and Napoleonic periods, most states in Germany elaborated new legal systems that tried to criminalize some forms of cruelty to animals. These reforms were preceded by public debates which aimed at mobilizing the whole society against the mistreatment of animals. In 1838, a Stuttgart clergyman, Albert Knapp, launched a nationwide call for the foundation of Societies for the prevention of cruelty to animals and he gained strong support for his proposal. This paper studies the religious, legal and philosophical motivations of this movement. In 1860, the first attempt to unify the local structures under an all-German umbrella institution failed. Only when the nation-state was created did o these initiatives in favour of centralization gain momentum.